2016
DOI: 10.4028/www.scientific.net/msf.840.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bath Temperature on Surface Properties of Anodised Titanium for Biomedical Application

Abstract: Anodic oxidation is an electrochemical method to deposit ceramic coatings on the metals substrate to improve the bioactivity. This study aims to investigate the effect of bath temperature on the surface properties of anodised titanium. High-purity titanium foil was modified by anodising in mixture of β-glycerophosphate disodium salt pentahydrate (β-GP) and calcium acetate monohydrate (CA). The experiments were carried out at 350 V, 30 mA.cm-2 for 10 minutes at different bath temperature (4-100 °C). Field emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Huang & Liu [193] prepared TiO 2 layer on pure titanium foils in 2 M NaOH in different bath temperatures and found worm-like nanostructures after anodising at 20 C, while short nanowire-like nanostructures were formed at 40 C and 60 C. Increased temperature increased the photoelectrochemical property of titanium oxide and this was attributed to the presence of sub-oxide species from the heated alkaline electrolyte causing nanotube growth to slow and thus structure on the surface became more compact, and this resulted in higher photocurrent. Lee et al [42] revealed that higher bath temperature will inhibit the formation of porous oxide layer since it favours the reactants during the anodic oxidation. Thereby, porous oxide layer will not be formed on the titanium anodised at higher bath temperature.…”
Section: Bath Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Huang & Liu [193] prepared TiO 2 layer on pure titanium foils in 2 M NaOH in different bath temperatures and found worm-like nanostructures after anodising at 20 C, while short nanowire-like nanostructures were formed at 40 C and 60 C. Increased temperature increased the photoelectrochemical property of titanium oxide and this was attributed to the presence of sub-oxide species from the heated alkaline electrolyte causing nanotube growth to slow and thus structure on the surface became more compact, and this resulted in higher photocurrent. Lee et al [42] revealed that higher bath temperature will inhibit the formation of porous oxide layer since it favours the reactants during the anodic oxidation. Thereby, porous oxide layer will not be formed on the titanium anodised at higher bath temperature.…”
Section: Bath Temperaturementioning
confidence: 99%
“…Lee et al. [ 42 ] revealed that higher bath temperature will inhibit the formation of porous oxide layer since it favours the reactants during the anodic oxidation. Thereby, porous oxide layer will not be formed on the titanium anodised at higher bath temperature.…”
Section: Factor Affecting Characteristics Of Tio 2 Layermentioning
confidence: 99%
See 1 more Smart Citation
“…From these applications viewpoints, the development of future nanocomposite requires the investigation of different elaboration pathway in order to promote synergetic effect between the nano compounds and to obtain a device cheaper and easier to be fabricated and handled. Titanium dioxide nanotube arrays are fabricated using anodic oxidation of titanium metal [16] [17] [18]. This electrochemical method is simple, cost effective and scalable.…”
mentioning
confidence: 99%